2020
DOI: 10.1177/1533033820947718
|View full text |Cite|
|
Sign up to set email alerts
|

Construction and Validation of Nomograms for Predicting the Prognosis of Juvenile Osteosarcoma: A Real-World Analysis in the SEER Database

Abstract: Background: Osteosarcoma is one of the most common malignant bone tumors, with a high incidence in adolescence. The objective of this study was to construct prognostic nomograms for predicting the prognosis of juvenile osteosarcoma. Methods: Patients with osteosarcoma diagnosed between 2004 and 2015 were identified in the Surveillance, Epidemiology, and End Results (SEER) database. The essential clinical predictors were identified with univariate and multivariate Cox analysis. Nomograms were constructed to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“… 31 However, a recent study of 736 adolescents with juvenile osteosarcoma from the SEER database demonstrated that the treatment of chemotherapy did not associate with improved OS as well as CSS. 32 In our study, we found that the elderly osteosarcoma patients without chemotherapy had an unfavorable prognosis, which was in accordance with previous studies for older patients. 33 , 34 Surgical resection of primary site plays a pivotal role in the management of patients with osteosarcoma.…”
Section: Discussionsupporting
confidence: 92%
“… 31 However, a recent study of 736 adolescents with juvenile osteosarcoma from the SEER database demonstrated that the treatment of chemotherapy did not associate with improved OS as well as CSS. 32 In our study, we found that the elderly osteosarcoma patients without chemotherapy had an unfavorable prognosis, which was in accordance with previous studies for older patients. 33 , 34 Surgical resection of primary site plays a pivotal role in the management of patients with osteosarcoma.…”
Section: Discussionsupporting
confidence: 92%
“…This has some enlightenment for doctors and patients in choosing surgical methods for patients with different risks. On chemotherapy, our study found that chemotherapy does not affect patient survival, similar to previous studies (38). highly consistent with the observed value, which indicates the accuracy of the prediction model.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that AJCC-Stage is composed of grade and AJCC-T/N/M, these variables form a high degree of collinearity ( Table S1 ) ( 26 , 27 ); thus the AJCC-Stage will not be included in univariate and multivariate analysis. Univariate analysis suggested that age, sex, pathological subtype (ICD-O-3 Hist/behave), primary site, grade, AJCC-T, AJCC-N, AJCC-M, tumor size, tumor extension, surgery type, radiation, and chemotherapy were significantly associated with CSS (all P≤0.05), whereas race, marital status, and laterality failed to reach statistical significance (P>0.05) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on surgery codes (https://seer. cancer.gov/manuals/2021/AppendixC/Surgery_Codes_ Bones_2021.pdf), the types of surgery were classified into local or partial resection (codes 15,19,25,26), radical resection with limb salvage (code 30), amputation (codes 40, 41, 42, 50), forequarter/hindquarter/hemipelvectomy (codes 51, 52, 53, 54), and surgery, NOS (code 90) (22,23).…”
Section: Data Extraction and Endpoint Definitionmentioning
confidence: 99%